Literature review of livable city within the framework of Maqasid al-Shar'iah: a preliminary study - Ibrahim, Ahmad Basri; Bostanooei, Aaesheh Mohammadi (Journal of Education and Social Science (JESOC), 2015)
Livability is defined as “quality of life” as experienced by the residents within the city or region. Therefore, the livability and quality of life is more subjective and intangible, as people perceive many different things when they speak of quality of living. While everyone agrees that a high crime rate is undesirable and the air we breathe, the house, the environment we live in should be clean, there is great diversity in ideas about quality of living, thus reflecting the different use of the term and different understanding depending on age, gender, religion, etc. Hence, it is crucial to explore the concept of livable city from the western viewpoint and Islamic viewpoint. In addition, it is also important to discover the criteria or factors of livability which are consistent with Maqasid of Shari’ah to give a clear picture of livable city in Islam. Before doing so however, it is crucial to study the literature review of this issue. As such, as a preliminary study of this topic, this paper will highlight the literature review of this topic.